Show the Step-by-Step Solution to the Equation

User Generated

Yvff90

Mathematics

Question Description

Please explain the steps to the problem.

6(-t+1)-4(2t-1)=t+4-5t

Student has agreed that all tutoring, explanations, and answers provided by the tutor will be used to help in the learning process and in accordance with Studypool's honor code & terms of service.

Explanation & Answer

6(-t+1)-4(2t-1)=t+4-5t

-6t + 6 - 8t + 4 = t + 4 - 5t

-14t + 10 = 4 - 4t

14t - 4t = 10 - 4

10t = 6

t = 6/10

t = 3/5


Npnqrzvpurycpragre (761)
Cornell University

Anonymous
Really useful study material!

Studypool
4.7
Trustpilot
4.5
Sitejabber
4.4